A Preliminary Study on the Application of Locally Produced Charcoal as the Activated Carbon for the Adsorption of Organic and Non-Organic Water Pollutants - Redzwan, Ghufran; Ali S, Rofeah; Yusof, Yushamida; Mohamed N, Marini (Malaysian Journal of Science, 2005)
Local charcoal (LC), which is derived from mangrove wood, was tested as the activated carbon (AC) for its adsorption capacity in wastewater treatment process. Synthetic wastewaters were prepared from solution of sapharine dye and chromium ions to simulate the organic and metal pollutants. The performance of LC was measured based on colour removal given by the spectrophotometer reading. The performance of LC was further compared with the other two analytical grades of activated carbon materials, namely BDH and Sigma. This study showed that local charcoal is more effective in removing Cr(III) solution, in which more than 90% could be removed. Meanwhile the performance of LC for the removal of dye solution was found to be inefficient. The removal efficiency was less than 10%. Therefore this study indicates that LC is more suitable to be used for the removal of metallic compound instead of organic substances. Further investigation with the use of phenol and glucose to simulate the aromatic and aliphatic organic substances, respectively, showed that LC is not as efficient as its ability to remove Cr(III) compared to removal of organic compounds.